Pembatalan Akta Notariil Oleh Notaris - Maria, Jenifer (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Notary is a public official that is inaugurated by a state to give legal and community services regarding civil law. Notary has several authorities, one of which is to make a written evidence in the form of authentic deed / notary deed. An authentic deed has a perfect evidentiary nature. An authentic deed is important in terms of creating a legal certainty, as an authentic deed can not be cancelled arbitrarily because of its nature as a state document. Therefore it is important to have a research regarding the cancellation of a notary deed by notary itself. This research is done by using normative juridical research method, with an approach using acts, regulations, and legal theories.